WORKSHOP STRATEGI MENGGALI IDE-IDE INOVATIF UNTUK MENGHASILKAN SKRIPSI YANG BERKUALITAS - Hasnawati; Nisa, Khairun; Novitasari, Setiani; Putri, Hikmah Ramdhani (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2025)
Thesis is one of the scientific papers that must be written by final year students, but many of them have difficulty in determining thesis topics that are innovative and relevant to current conditions. This community service activity aims to provide assistance through a workshop on strategies to explore innovative ideas in order to produce quality theses for PGSD FKIP University of Mataram students. The stages in this workshop activity are starting from the coordination stage, promotion stage, implementation stage and evaluation and reporting stage. The methods of implementing the workshop activities include interactive lectures, discussions, and idea development exercises based on case studies and the context of elementary education. This workshop activity was carried out at campus 2 FKIP University of Mataram on August 24, 2024. The results of the activity showed that participants gained a good understanding of how to find innovative, original and contextual thesis topics. In addition, this workshop can also increase students' self-confidence and readiness in facing the thesis writing process. Based on the results of the participants' responses to the workshop activities carried out, on average students gave positive responses. This activity is expected to become a sustainable program that supports improving the quality of theses and completing studies on time for PGSD students.